Consensus Definitions and Interpretation Templates for Fluoroscopic Imaging of Defecatory Pelvic Floor Disorders: Proceedings of the Consensus Meeting of the Pelvic Floor Consortium of the American Society of Colon and Rectal Surgeons, the Society of Abdominal Radiology, the International Continence Society, the American Urogynecologic Society, the International Urogynecological Association, and the Society of Gynecologic Surgeons. Issue 1 (January 2021) - Paquette, Ian; Rosman, David; El Sayed, Rania; Hull, Tracy; Kocjancic, Ervin; Quiroz, Lieschen; Palmer, Susan; Shobeiri, Abbas; Weinstein, Milena; Khatri, Gaurav; Bordeianou, Liliana
Abstract : Supplemental Digital Content is available in the text.